Pelatihan Mesin Es Krim FOMAC ICR-BQ108 untuk Meningkatkan Kualitas Produk pada UMKM Es Boba Indonesia - Hilmi Iman Firmansyah; Fauzan Baananto; Bayu Pranoto; Chandra Gunawan; Sulistyono; Imam Mashudi (Jurnal Pengabdian kepada Masyarakat, 2025)
Es Boba Indonesia, a small and medium enterprise (SME) in Malang, experienced challenges in producing high-quality ice cream due to malfunctions in the FOMAC ICR-BQ108 ice cream machine. The primary issue was that the ice cream melted quickly and did not have the desired soft texture, which negatively affected competitiveness. This community service program aimed to repair the machine through a series of steps, including damage identification, repair, and performance optimization. Post-repair results showed significant improvements in ice cream quality and machine operational efficiency, accompanied by training for the partner to ensure sustainable maintenance.